2020
DOI: 10.1007/s10592-020-01255-9
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia and Cardinium infection found in threatened unionid species: a new concern for conservation of freshwater mussels?

Abstract: Endosymbiotic bacterial species that manipulate host biology, reproduction and mitochondrial genetic diversity have been identified in many metazoans, especially terrestrial arthropods. Until now, the hypothesis that Wolbachia or other bacterial endosymbiont might be absent in mollusks has remained unexplored. We present here preliminary data on bacterial communities in a freshwater mussel Unio crassus-species with doubly uniparental inheritance of mtDNA (DUI). Next generation sequencing of 16S rRNA bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This OTU was especially abundant in controls representing nearly half (45%) of all recovered sequences in those digestive glands, and was the only OTU significantly associated with this group via indicator species analysis. Rickettsia-like organisms have been sporadically reported via histological examination of the digestive gland of mussels previously (Mioduchowska et al 2020;Burcham et al 2023) and could represent an important commensal in healthy tissue. This rickettsial OTU was also found with high relative abundance in the hemolymph of controls while lower in hemolymph of both case groups (Case-Present, Case-Absent) and warrants further investigation for use as a potential indicator of mussel health.…”
Section: Discussionmentioning
confidence: 99%
“…This OTU was especially abundant in controls representing nearly half (45%) of all recovered sequences in those digestive glands, and was the only OTU significantly associated with this group via indicator species analysis. Rickettsia-like organisms have been sporadically reported via histological examination of the digestive gland of mussels previously (Mioduchowska et al 2020;Burcham et al 2023) and could represent an important commensal in healthy tissue. This rickettsial OTU was also found with high relative abundance in the hemolymph of controls while lower in hemolymph of both case groups (Case-Present, Case-Absent) and warrants further investigation for use as a potential indicator of mussel health.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Sironi et al [33] found a Wolbachia-like organism in Nematoda for the very first time. In 2018-2021, our team discovered Wolbachia infections in Tardigrada [34], Bivalvia [35] and Crustacea [32]. Later, Tibbs-Cortes et al [36] also confirmed Wolbachia infection in the microbiome of Tardigrada.…”
Section: Supergroup Host Host-wolbachia Association Referencementioning
confidence: 91%
“…The only Wolbachia sequences in bivalves were those reported by Mioduchowska et al [35] for U. crassus. These sequences have been clustered in a clade containing a possible new strain, which is here named supergroup V. In this study, Wolbachia was rediscovered in U. crassus (previously reported in [35]) and was discovered for the first time in D. polymorpha. Both infections were detected using our designed primers.…”
Section: Wolbachia In Freshwater Bivalviamentioning
confidence: 95%
“…However, no standard set of biomarkers or other diagnostic tools exist to assess mussel health in response to a wide range of known and unknown stressors. Because mussels are filter feeders, their symbiotic microbiome also may be sensitive to environmental conditions and could provide additional insight about overall health status (Aceves, 2019 ; McCauley et al, 2021 ; Mioduchowska et al, 2020 ; Weingarten et al, 2019 ). A standardized diagnostic approach specific to mussels is needed that can identify clinical signs of compromised health.…”
Section: Theme: Autecologymentioning
confidence: 99%
“…Pathogens, including trematodes, nematodes, mites, ciliates, bacteria, and viruses can have a wide range of negative effects on mussels (and other species), including catastrophic mortality (Brian & Aldridge, 2019 ; Richard et al, 2020 ; Taskinen et al, 1997 ). In addition, bacterial endosymbionts, that is, Wolbachia and Cardinium , recently recorded in the threatened Unio crassus (Mioduchowska et al, 2020 ), can significantly increase parthenogenesis and female‐biased sex ratios through feminization, male killing, and cytoplasmic incompatibility. The infection and severity of these endosymbionts are expected to be affected by climate change (Charlesworth et al, 2019 ).…”
Section: Theme: Population Dynamicsmentioning
confidence: 99%